The Effect of Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) on Price to Book Value (PB) in Mining Subsector Companies Listed on the Indonesian Stock Exchange (IDX) for the 2020-2024 Period - Nurbaiti, Nikmah; Dhea Parlina, Nurhana (Journal Research of Social Science, Economics, and Management, 2026)
Study This aim For analyze The influence of Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) on Price to Book Value (PBV) in companies subsector mining companies listed on the Indonesia Stock Exchange ( IDX) for the 2020–2024 period . Research use approach quantitative with design associative . Population study covering 42 companies subsector mining , with purposive sampling technique so that obtained by 10 companies as sample study for five years observations , resulting in a total of 50 observations . The data used is secondary data in the form of report finance analyzed annually? use multiple linear regression through device SPSS software version 22. Research results show that in a way partial Return on Assets (ROA) and Current Ratio (CR) have an effect positive and significant on Price to Book Value (PBV), while Debt to Equity Ratio (DER) has an effect negative and significant towards PBV. In general simultaneously , ROA, CR, and DER have an effect significant on PBV. Findings This indicates that profitability , liquidity , and structure capital is factor important things that influence mark company subsector mining . Companies with level good profitability and liquidity? as well as low leverage levels tend own mark more companies? high in the eyes of investors.content analysis